Substitution of mineral fertilizers with biofertilizer: an alternate to improve the growth, yield and functional biochemical properties of strawberry (Fragaria × ananassa Duch.) cv. Camarosa. (14th September 2019) - Kumar, Santosh; Kundu, Manoj; Das, Anupam; Rakshit, Rajiv; Siddiqui, Md. Wasim; Rani, Ruby
Abstract: An experiment was conducted to substitute mineral fertilizers with biofertilizers in strawberry to work out the yield, quality of strawberry and soil fertility. A 25% substitution of mineral fertilizer with biofertilizer increased the number of fruits/plant along with improving Juice content (89.55%), Total soluble solids (10.35°B), total sugar (6.69%), ascorbic acid (43.80 mg 100 g −1 ), anthocyanin content (81.05 mg 100 g −1 ), total phenol (5.97 mg Gallic acid equiv. g −1 ), flavonoids (0.12 mg g −1 ) and antioxidant capacity (2.13 µmol. Trolox equiv. 100 g −1 ). The available N and K content in post-harvest soils were improved significantly with 75% RDF + Azospirillium @ 2 g plant −1 + PSB @ 2 g plant −1 + topdressing of 25% K treatments (200.10 and 211.70 kg ha −1, respectively). Viable count of soil microorganisms (Bacteria, actinomycetes and fungi) was also estimated maximum (4066, 190 and 11.33 × 10 4 cfu g −1  dry soil, respectively) with substitution of 25% of mineral fertilizer either with Azotobacter or Azospirillum .